Work with, within and for the City - Marques, César; Silva, Fernando; Cardoso, Graça; Liberato, Helena; Lopes, Hilário; Caramelo, José; João, José; Santos, Liliete; Reverendo, Marta; Jorge, Susana; Lourenço, Reinaldo (Open Schools Journal for Open Science, 2019)
Our school and classes do not have boundaries. In this project, students worked in the same projects in Civics, English Language, Information and Communication Technology, Mathematics, Physics and Chemistry and Portuguese Language classes. They worked on real daily life problems in Cacilhas, identified problems, did field work, talked with people, searched for solutions.